2017
DOI: 10.1371/journal.pone.0187612
|View full text |Cite
|
Sign up to set email alerts
|

Association of high-risk sexual behaviour with diversity of the vaginal microbiota and abundance of Lactobacillus

Abstract: ObjectiveTo compare the vaginal microbiota of women engaged in high-risk sexual behaviour (sex work) with women who are not engaged in high-risk sexual behaviour. Diverse vaginal microbiota, low in Lactobacillus species, like those in bacterial vaginosis (BV), are associated with increased prevalence of sexually transmitted infections (STIs) and human immunodeficiency virus (HIV) acquisition. Although high-risk sexual behaviour increases risk for STIs, the vaginal microbiota of sex workers is understudied.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 73 publications
3
52
4
Order By: Relevance
“…Lack of association between Nugent score and vaginal microbiome composition in our study is surprising but has previously been reported. 28 Various factors can contribute to this discrepancy in findings, for example, different methods of Gram staining may result in different Nugent score inter-rater reliability 29 and low abundance of bacteria that are better represented by sequencing than Nugent score. 30 Figure 2.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of association between Nugent score and vaginal microbiome composition in our study is surprising but has previously been reported. 28 Various factors can contribute to this discrepancy in findings, for example, different methods of Gram staining may result in different Nugent score inter-rater reliability 29 and low abundance of bacteria that are better represented by sequencing than Nugent score. 30 Figure 2.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial DNA was extracted and purified from CVL supernatants as described (21). Four 1 mL aliquots of PBS (negative controls) were randomly selected for gDNA extraction and PCR amplification of the 16S rRNA gene.…”
Section: Methodsmentioning
confidence: 99%
“…Four 1 mL aliquots of PBS (negative controls) were randomly selected for gDNA extraction and PCR amplification of the 16S rRNA gene. The hypervariable V3 region of 16S was amplified by PCR (21, 51). PCR products were sequenced by McMaster Genomics Facility (Hamilton, ON), Illumina MiSeq platform.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations